Production Function According to Yusuf Qardhawi in Islamic Economics - Trisna Taufik Darmawansyah; Husnayaini Amalia; Yani Aguspriyani (Fakultas Ekonomi dan Bisnis Islam, 2022)
Economic activities, one of which is production, is taught in the Qur'an. In the context of Islamic economics, a Muslim producer must behave in accordance with the norms and ethics of Islamic economic production. It takes a knowledge and understanding of production behavior according to Islam in order to fulfill this behavior. Knowledge of a concept greatly influences a person's behavior. Yusuf Qardhawi's thoughts on the factors of production are that production only has two main elements, namely natural resources and human resources in the form of labor. Yusuf Qardhawi further explained that natural resources are very much needed to be managed by humans, therefore, in production, labor is needed. New production appears when there is a combination of work between human resources and natural resources. While the capital factor is not included in the main factor because capital is nothing more than the result of human labor that is stored. Another reason capital is not included is because this problem is related to usury which is forbidden. Meanwhile, other elements such as organization are only supervision, regulation and production strategy.